Assessment of Toxoplasma gondii lytic cycle and the impact of a gene deletion using 3D label-free optical diffraction holotomography - Koutsogiannis, Zisis; Mina, John G. M.; Suman, Rakesh; Denny, Paul William (Frontiers in Cellular and Infection Microbiology, 2023)
Toxoplasma gondii is a widespread single-celled intracellular eukaryotic apicomplexan protozoan parasite primarily associated with mammalian foetal impairment and miscarriage, including in humans. Is estimated that approximately one third of the human population worldwide is infected by this parasite. Here we used cutting-edge, label-free 3D quantitative optical diffraction holotomography to capture and evaluate the Toxoplasma lytic cycle (invasion, proliferation and egress) in real-time based on the refractive index distribution. In addition, we used this technology to analyse an engineered CRISPR-Cas9 Toxoplasma mutant to reveal differences in cellular physical properties when compared to the parental line. Collectively, these data support the use of holotomography as a powerful tool for the study of protozoan parasites and their interactions with their host cells.